Kabbala : an Introduction to Jewish Mysticism and Its Secret Doctrine. - Bischoff, Erich (Weiser classics series., 2014)
The author uses a question and answer format to provide basic background information for the study of Kabbals. Includes history, doctrines, anthropology, magical methods, talismans, and shows the growth and change within the movement.